Cold shock stress-induced proteins in Bacillus subtilis. - Graumann, P (1996)
Bacteria respond to a decrease in temperature with the induction of proteins that are classified as cold-induced proteins (CIPs). Using two-dimensional gel electrophoresis, we analyzed the cold shock response in Bacillus subtilis. After a shift from 37 to 15 degrees C the synthesis of a majority of proteins was repressed; in contrast, 37 proteins were synthesized at rates higher than preshift rates. One hour after cold shock, the induction of CIPs decreased, and after 2 h, general protein synthesis resumed. The identified main CIPs were excised from two-dimensional gels and were subjected to microsequencing. Three small acidic proteins that showed the highest relative induction after cold shock were highly homologous and belonged to a protein family of which one member, the major cold shock protein, CspB, has previously been characterized. Two-dimensional gel analyses of a cspB null mutant revealed that CspB affects the level of induction of several CIPs. Other identified CIPs function at various levels of cellular physiology, such as chemotaxis (CheY), sugar uptake (Hpr), translation (ribosomal proteins S6 and L7/L12), protein folding (PPiB), and general metabolism (CysK, Ilvc, Gap, and triosephosphate isomerase).